PENERAPAN APLIKASI TEKNOLOGI KOMUNIKASI DAN INFORMASI DI PONDOK PESANTREN RAUDHATUL ULUM SAKA TIGA OGAN ILIR SUMATERA SELATAN - Suryati Suryati; Adisel Adisel (Jurnal Komunikasi Islam dan Kehumasan (JKPI), 2020)
The purpose of this study is to describe the application of information technology and communications in Raudhatul Ulum Sakatiga Islamic Boarding school South Sumatra. This research method is descriptive qualitative research. Data collection techniques using participant observation, interview and documentation. Data analysis procedure performed by the display, reduction, categorisation, syntesis, and hypothesis data. The results of this study are; (1)the application of ICTs, (2)the process of planning,implementation and evaluation, (3)the process of integrating ICT, (4)ICT be used as a learning tool, administration and as media promotio, (5) optimize the role of ICT, (6) the constraints on its implementation. Based on the results, this study offers some recommendations, namely,;boarding school must immediately address the issue of lack of power, and hold a new Client Server with a larger capacity.